Unveiling the Enigmatic CYP3A4 Enzyme : A Literature Review: English - Saragih, Daniel S. Pandapotan; Muhammad Ichwan (Talenta Publisher, 2025)
Cytochrome P450 3A4 (CYP3A4) is a crucial enzyme in the human body, primarily responsible for endobiotic and xenobiotic metabolism, including many commonly prescribed medications. It plays a pivotal role in the biotransformation of more than 50% of drugs. But the high frequency of genetic polymorphisms in the CYP3A4 gene contributes to significant interindividual variability in enzyme activity. These genetic variations can affect drug metabolism rates, leading to altered pharmacokinetics and necessitating dose adjustments for certain medications, particularly in populations with different allele frequencies. The impact of these genetic variants can vary significantly across different ethnicities, highlighting the importance of pharmacogenetic testing in personalized medicine. However, there is currently a lack of a comprehensive study examining this variability across different ethnicities. This review will help understand these genetic differences across population and ethnicity to allow healthcare providers to tailor drug therapies to individual genetic profiles, enhancing treatment efficacy and safety.